2012
DOI: 10.1101/gad.181826.111
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombeCcq1 and TER1 bind the 14-3-3-like domain of Est1, which promotes and stabilizes telomerase–telomere association

Abstract: The telomerase protein Est1 exists in multiple organisms, including Schizosaccharomyces pombe, humans, and Saccharomyces cerevisiae, but its function has only been closely examined in S. cerevisiae, where it is a recruiter/activator of telomerase. Here, we demonstrate that S. pombe Est1 was required for the telomere association of the telomerase holoenzyme, suggesting that it too has a recruitment role. Its association with telomeres was dependent on Trt1, the catalytic subunit, and Ccq1, a telomeric protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 42 publications
(76 reference statements)
4
56
1
Order By: Relevance
“…Telomerase recruitment to telomeres in S. pombe occurs through the interaction of the telomerase subunit Est1 with Ccq1, which is tethered to telomeres through the interaction with Tpz1, which in turn interacts with Pot1 and Poz1 (Miyoshi et al 2008;Tomita and Cooper 2008;Webb and Zakian 2012). Importantly, S. pombe Tel1 (ortholog of mammalian Atm) and Rad3 (ortholog of mammalian Atr) promote the direct interaction between Ccq1 and the Est1 subunit of telomerase (Moser et al 2011;Yamazaki et al 2012).…”
Section: S Pombementioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase recruitment to telomeres in S. pombe occurs through the interaction of the telomerase subunit Est1 with Ccq1, which is tethered to telomeres through the interaction with Tpz1, which in turn interacts with Pot1 and Poz1 (Miyoshi et al 2008;Tomita and Cooper 2008;Webb and Zakian 2012). Importantly, S. pombe Tel1 (ortholog of mammalian Atm) and Rad3 (ortholog of mammalian Atr) promote the direct interaction between Ccq1 and the Est1 subunit of telomerase (Moser et al 2011;Yamazaki et al 2012).…”
Section: S Pombementioning
confidence: 99%
“…These subunits are not involved per se in catalysis, but they are important for telomerase assembly or the recruitment to telomeres. The S. cerevisiae Est1, which recruits telomerase to telomeres (discussed below), has a clear counterpart in S. pombe (Beernink et al 2003;Webb and Zakian 2012), but the orthologous relationship to human Est1-like proteins (referred to as Est1A/Smg6, Est1B/ Smg5, and Est1C/Smg7) is uncertain (Reichenbach et al 2003;Snowet al 2003). Est1A interacts as the budding and fission yeast Est1 proteins with telomerase, but a role in telomerase recruitment has not been shown (Redon et al 2007).…”
Section: Telomerasementioning
confidence: 99%
“…We previously showed that the terminus of the long TER1 arm binds Est1 (ever shorter telomeres protein 1) (16). The other region splits into two arms: One arm binds Sm and Lsm proteins (17), and the other is uncharacterized.…”
Section: Resultsmentioning
confidence: 99%
“…Southern and Northern blotting were performed as previously described (16). RNA immunoprecipitation and ChIP were performed as previously described (16). In vitro telomerase assays were performed as in ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation